2018
DOI: 10.1063/1.5038721
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy studies of PTCDI on Ag/Si(111)-3×3

Abstract: 3,4,9,10-perylene tetracarboxylic diimide molecules were evaporated onto a Ag/Si(111)-3×3 surface and studied using photoelectron spectroscopy and near edge X-ray absorption fine structure (NEXAFS). All core levels related to the imide group of the molecules showed a partial shift to lower binding energies at low coverages. In NEXAFS spectra, the first transitions to the unoccupied states were weaker at low coverages compared to thicker films. Also, extra states in the valence band between the regular highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In the previous study, the interaction was also investigated using NEXAFS where it was concluded that due to the filling of the LUMO the first transitions to the LUMO are heavily suppressed at PTCDI coverages up to 1 ML. 14 The changes in NEXAFS spectra and extra states in the valence band close to the Fermi level are similar to what was observed for 1 ML coverage of PTCDA on Ag(111) 24 and Ag(110). 24,25 In those studies, it was also suggested that the changes were due to the LUMO of the molecules being filled or partially filled due to charge donation from the substrate to the molecules.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…In the previous study, the interaction was also investigated using NEXAFS where it was concluded that due to the filling of the LUMO the first transitions to the LUMO are heavily suppressed at PTCDI coverages up to 1 ML. 14 The changes in NEXAFS spectra and extra states in the valence band close to the Fermi level are similar to what was observed for 1 ML coverage of PTCDA on Ag(111) 24 and Ag(110). 24,25 In those studies, it was also suggested that the changes were due to the LUMO of the molecules being filled or partially filled due to charge donation from the substrate to the molecules.…”
supporting
confidence: 76%
“…In the previous studies, the states close to the Fermi level were preliminary investigated using STS 11 and angular integrated UPS. 14 In both studies, the states L and H states were found at similar energy positions of around −0.3 and −2.5 eV relative to the Fermi level at 1 ML PTCDI coverage. The main problem was the H state that was found at −1.2 eV in the STS study and at −1.5 eV in the UPS study.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Peak C (287.2 eV) and peak D (287.9 eV) arise from the resonant excitations of carbonyl C 1s into LUMOs. For the N K-edge region, the sharp peak at 400.8 eV (peak E) belongs to the transition from the imide nitrogen atoms into LUMO+1 [41,42]. The peak for the transition from N 1s to LUMO is too weak to be observed for PTCDI due to the forbidden symmetry during the X-ray absorption process [42].…”
Section: Resultsmentioning
confidence: 99%
“…For the N K-edge region, the sharp peak at 400.8 eV (peak E) belongs to the transition from the imide nitrogen atoms into LUMO+1 [41,42]. The peak for the transition from N 1s to LUMO is too weak to be observed for PTCDI due to the forbidden symmetry during the X-ray absorption process [42]. After the deposition of 0.4 nm Li, peak A attenuates apparently in intensity because the original LUMO is occupied by the electrons donated by Li.…”
Section: Resultsmentioning
confidence: 99%